Implementing New Era Life Order in Harper Kuta Hotel - Anak Agung Kompiang Trijaya Putra; Ni Made Ernawati; I Made Darma Oka (Catuspata Press, 2021)
Abstract : Purpose: This study is to identify the implementation of the new era life order in Harper Kuta Hotel, Bali, Indonesia due to Covid-19 pandemic. Research methods: This study uses descriptive qualitative methods supported by the data from respondents collected collectively using the google form platform, which is then reduced and summarized from all existing opinions. Findings: The new era of life in Harper Kuta Hotel is taking place positively. It is according to the existing standard operating procedures. The creation of the new standard operating procedures is adjusted to the guidelines issued by the Bali Provincial Tourism Office which are used as guidelines in carrying out verification. Implications: There are some additions and adjustments to existing standards both in terms of products and services, as well as from the use cycle of elements that come into contact with guests.